The Influence of Thrombin on the Clotting Activity of Factor VIII. A Study with Insolubilized Thrombin - Vukovich, Th; Koller, E; Doleschel, W (Thrombosis and Haemostasis, 1978)
An investigation of the influence of thrombin on the clotting activity of factor VIII was made. Purified factor VIII and different amounts of thrombin complexed to Sepharose 4 B were mixed and incubated for various periods of time. The factor VIII activities of these incubation mixtures were determined by the one- and two-stage analytical procedures in the presence of the thrombin-sepharose and in its absence following the latter removal from the test sample by filtration. The results so obtained confirm the view that thrombin inactivates factor VIII. Evidences for a thrombin-induced potentiation of the factor VIII activity, seen only in the thrombin-sepharose containing test samples analyzed by the one-stage method, are here interpreted as thrombin-effects peculiar to this factor VIII test system and not as potentiation by thrombin of the factor itself.